2014
DOI: 10.1097/01.tp.0000440953.06886.a3
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Variants With Rapid Fibrosis

Abstract: Background Recurrence of hepatitis C, the main indication for liver transplantation in the United States, leads to rapid fibrosis progression and worse outcomes compared to other indications. While clinical variables play a role, they are insufficient to explain all inter-patient variability in posttransplant fibrosis progression. Genetic factors associated with hepatitis C virus (HCV) outcomes have been identified, but limited studies have been conducted in the context of HCV-related liver transplantation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Few data regarding the effect of genetic predisposition for FP exist in post-transplant patients. Layden et al [14] identified significant multivariate associations of FP in post-transplant HCV-infected patients with recipient gene variants of the interleukin 28B (IL28B), DEAD box protein 5 (DDX5), patatinlike phospholipase domain containing 3 (PNPLA3), suppressor of cytokine signaling-3 (SOCS3) and malectin (MLEC) genes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Few data regarding the effect of genetic predisposition for FP exist in post-transplant patients. Layden et al [14] identified significant multivariate associations of FP in post-transplant HCV-infected patients with recipient gene variants of the interleukin 28B (IL28B), DEAD box protein 5 (DDX5), patatinlike phospholipase domain containing 3 (PNPLA3), suppressor of cytokine signaling-3 (SOCS3) and malectin (MLEC) genes [14].…”
Section: Introductionmentioning
confidence: 99%